Regeneration of the Built Environment from a Circular Economy Perspective - Della Torre, Stefano; Cattaneo, Sara; Lenzi, Camilla; Zanelli, Alessandra (Research for Development, 2020)
This open access book explores the strategic importance and advantages of adopting multidisciplinary and multiscalar approaches of inquiry and intervention with respect to the built environment, based on principles of sustainability and circular economy strategies. A series of key challenges are considered in depth from a multidisciplinary perspective, spanning engineering, architecture, and regional and urban economics. These challenges include strategies to relaunch socioeconomic development through regenerative processes, the regeneration of urban spaces from the perspective of resilience, the development and deployment of innovative products and processes in the construction sector in order to comply more fully with the principles of sustainability and circularity, and the development of multiscale approaches to enhance the performance of both the existing building stock and new buildings. The book offers a rich selection of conceptual, empirical, methodological, technical, and case study/project-based research. It will be of value for all who have an interest in regeneration of the built environment from a circular economy perspective.